Biology of Lysiphlebus fabarum following cold storage of larvae and pupae. Issue 1 (21st July 2014) - Mahi, Hossein; Rasekh, Arash; Michaud, J.P.; Shishehbor, Parviz
Abstract Cold storage is one means of preserving parasitoids prior to release in augmentation biological control programs. This study examined the feasibility of storing larval and pupal stages of a sexual population of Lysiphlebus fabarum Marshall (Hymenoptera: Braconidae: Aphidiinae) at 6 ± 1 and 8 ± 1 °C, 50–60% r.h., and L14:D10 photoperiod. These life stages were stored for periods of 1, 2, and 3 weeks under fluctuating thermal regimes (2 h daily at 21 ± 1 °C). Generally, pupae gave better results than larvae, and 6 °C was better than 8 °C, considering wasp survival, wasp size (tibial and antennal lengths), egg load, and egg size. The best results were obtained with pupae stored for 2 weeks under a fluctuating temperature regime at 6 °C. Females emerging from this treatment did not differ from controls (developing directly at 21 °C) in body size, egg size, or progeny sex ratio, and suffered less than 20% mortality. Egg loads were reduced in these wasps, but the reductions were substantially less than occurred in other 2‐week‐storage treatments. Wasps stored in this manner successfully parasitized similar numbers of aphids as controls and produced similar progeny sex ratios. These results reveal a suitable set of low‐temperature conditions that can be used to delay the development of L. fabarum for 2 weeks with minimal impact on wasp fitness.